Development of Ferrocenyl and Ruthenocenyl Zileuton Analogs with Enhanced Bioactivity Toward Human 5-Lipoxygenase: Innovation in Drugs for Inflammatory Diseases - Mascayano-Collado, C; Godoy-Gonzalez, F; Godoy-Gonzalez, F; Navarrete-Tudela, E (American Chemical Society, 2025)
Zileuton is the only FDA-approved 5-lipoxygenase (5-LOX) inhibitor for asthma treatment, but it produces hepatotoxicity associated with the benzothiophene fragment. Using the concept of organometallic derivatization pioneered by Jaouen and Brocard, we synthesized five new organometallic Zileuton derivatives, maintaining the urea fragment and incorporating ferrocenyl and ruthenocenyl moiety (3a−e). Their biological activity was evaluated against 5-LOX, 15-LOX, COX-1, and COX-2 enzymes. The ferrocenyl and ruthenocenyl N-hydroxyurea complexes coined Ferroleuton (3a) and Ruthenoleuton (3e) showed the highest selective inhibitory activity against 5-LOX, with IC50 values of 0.21 ± 0.12 and 3.49 ± 1.11 μM, respectively. Notably, 3a exhibited superior activity compared to Zileuton (IC50 0.67 ± 0.09 μM), demonstrating the key role of N-hydroxyurea and ferrocenyl fragments in the inhibitory process. Worthy of note, both compounds displayed low cytotoxicity in lung fibroblast healthy cells line (MRC-5) (CC50 of 116.40 and >200 μM, respectively). Enzyme kinetic studies indicated competitive and mixed types of inhibition for 3a and 3e, respectively. Additionally, they demonstrated superior antioxidant capacity compared to Zileuton (DPPH, ABTS, and FRAP assays). Electrochemical and molecular dynamics (MD) studies suggest a chelating-redox deactivation mechanism for 5-LOX. These findings position Ferroleuton (3a) and Ruthenoleuton (3e) as promising candidates for inflammatory disease treatment. © 2025 American Chemical Society.